14‐Color single tube for flow cytometric characterization of CD5+ B‐LPDs and high sensitivity automated minimal residual disease quantitation of CLL/SLL. Issue 4 (8th September 2020) - Goshaw, Jennifer M.; Gao, Qi; Wardrope, Jessica; Dogan, Ahmet; Roshal, Mikhail
Abstract: Introduction: The diagnosis of CLL/SLL relies on flow cytometric immunophenotyping. Increasing emphasis is being placed on precise detection of the minimal residual disease. Following antigen recommendations of ERIC and ESCCA's Harmonization Project, we validated a 14‐color assay for the characterization CD5+ lymphoproliferative neoplasms and CLL MRD with a sensitivity of at least 10 −4 . Methods: The assay was designed based on ERIC/ESCCA recommended antigens with the addition of CD40 for alternate gating when CD19 expression is reduced. Lower limit of quantitation/lower limit of detection, assay procedural precision, linearity, and limit of blank were established. Then, 52 CD5+ B‐cell lymphoproliferative neoplasms (41 CLL/11 non‐CLL) and 29 normal samples were used for parallel evaluation. Automated cluster identification and quantitation of CLL clones in MRD setting was performed using Barned‐Hutt SNE. Separation analysis between CLL and non‐CLL phenotypes was performed by PCA and bh‐SNE. Results: Separation ratios for each antigen exceeded ERIC/ESCCA guidelines. Precision was <20% at LLOQ (0.01%). The limit of blank was <10/500, 000 cells. Concordance between the 14‐color and legacy assay (Deming regression y = 1.01x, r 2 = .99) was seen. All 20 samples with MRD levels 0.5%–0.006% (median 0.04%) showed an abnormal cell cluster by bh‐SNE, with concordant results between manual and automated quantitation ( y = x, r 2 = 1). CLL cases clustered together and away from mantle cell lymphoma by bh‐SNE and PCA with outlier atypical phenotype CLL cases posing diagnostic challenges by both manual and automated analysis. Conclusion: The 14‐color CD5+ LPD assay provides a robust standardization platform for MRD and disease characterization using both manual and automated analysis.